2010
DOI: 10.1016/j.bcp.2010.01.023
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Thymoquinone poly (lactide-co-glycolide) nanoparticles exhibit enhanced anti-proliferative, anti-inflammatory, and chemosensitization potential

Abstract: Thymoquinone (TQ), derived from the medicinal spice Nigella sativa (also called black cumin), has been shown to exhibit anti-inflammatory and anti-cancer activities. In this report we employed polymer-based nanoparticle approach to improve upon its effectiveness and bioavailability. TQ was encapsulated with 97.5% efficiency in biodegradable nanoparticulate formulation based on poly (lactide-co-glycolide) (PLGA) and the stabilizer polyethylene glycol (PEG)-5000. Dynamic laser light scattering and transmission e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(77 citation statements)
references
References 39 publications
2
73
0
2
Order By: Relevance
“…The principal phytochemicals of NSSEO are thymoquinone, p-cymene, α-pinene, thymohydroquinone, dithymoquinone and nigellone (Al Juhaimi et al, 2013). In fact, thymoquinone formed the main part of NSSEO to which mostly NSSEO therapeutic usages are attributed to it (Ravindran et al, 2010). It is reported that the production of inflammatory cytokines can be inhibited by thymoquinone in NSSEO (Ahmad et al, 2013).…”
Section: Introduction:-mentioning
confidence: 99%
“…The principal phytochemicals of NSSEO are thymoquinone, p-cymene, α-pinene, thymohydroquinone, dithymoquinone and nigellone (Al Juhaimi et al, 2013). In fact, thymoquinone formed the main part of NSSEO to which mostly NSSEO therapeutic usages are attributed to it (Ravindran et al, 2010). It is reported that the production of inflammatory cytokines can be inhibited by thymoquinone in NSSEO (Ahmad et al, 2013).…”
Section: Introduction:-mentioning
confidence: 99%
“…In a previous study, Ravindran et al, (2010) succeeded in loading TQ into a poly (lactide-co-glycolide) nanoparticle. Other attractive nanocarriers are liposomes.…”
Section: Original Articlementioning
confidence: 99%
“…Treatment of TQ at 10 mM induced inhibition of cell growth by 15% compared with the control (Ravindran et al 2010). In contrast to MDA-MB-231, MCF-7 has an estrogen receptor and expresses wild-type p53, a tumor-suppressor protein.…”
Section: Discussionmentioning
confidence: 92%